Spatial Development - Desmet, Klaus; Rossi-Hansberg, Esteban (American Economic Review, 2014)
We present a theory of spatial development. Manufacturing and services firms located in a continuous geographic area choose each period how much to innovate. Firms trade subject to transport costs and technology diffuses spatially. We apply the model to study the evolution of the US economy in the last half-century and find that it can generate the reduction in the manufacturing employment share, the increased spatial concentration of services, the growth in service productivity starting in the mid-1990s, the rise in the dispersion of land rents in the same period, as well as several other spatial and temporal patterns. (JEL J21, L16, L60, L80, O33, R11, R32)